Salvage treatment in recurrent endometrial cancer of the pelvis and peritoneal cavity - Lindsey A. McAlarnen; Kelly Ryan; William Adams; Adam Gliniewicz; Abigail D. Winder; Margaret R. Liotta; Ronald K. Potkul; William Small, Jr; Matthew M. Harkenrider (Elsevier, 2019)
Regional recurrence of endometrial cancer is a challenging yet potentially curable group of patients without defined standard of care. Our aim is to determine optimal methods of salvage therapy for regionally recurrent endometrial cancer.Twenty-two cases of nodal, pelvic, or peritoneal cavity recurrences of endometrial cancer were identified from a single institution database. Univariable Cox proportional hazards models were used to estimate the risk of a second recurrence or death. Kaplan-Meier plots were used to estimate the probability of progression free survival and overall survival among patients in three cohorts: Multimodality therapy (surgery, chemotherapy, and external beam radiotherapy [EBRT] +/− vaginal brachytherapy), non-surgery (chemotherapy or EBRT, or both), and surgery cohort (surgery +/− chemotherapy OR EBRT).Thirteen recurrences (59%) were regional including the pelvic and paraaortic nodes, while nine recurrences (41%) were abdominal. For the entire cohort, the probability of progression free survival at 2 years was 51% (95% CI, 26% - 72%). The 2-year probability of progression free survival was 62% in the multimodality cohort, 40% in the non-surgery cohort, and 38% in the surgery cohort. The 2-year probability of overall survival was 69% (95% CI, 38% - 86%) across our population. At 40 months of follow up, the only living patients belonged to the multimodality cohort.We found no significant association of a definitive salvage regimen for recurrent endometrial cancer of the pelvis and peritoneal cavity. Aggressive use of multimodality therapy with surgery followed by tumor-directed radiotherapy and chemotherapy offers potentially curative therapy for these patients. Keywords: Salvage therapy, Recurrent endometrial cancer, Cytoreductive surgery, Multimodality treatment